Therapeutic application of hydrogels for bone-related diseases - Liu, Xiyu; Sun, Shuoshuo; Wang, Nan; Kang, Ran; Xie, Lin; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Bone-related diseases caused by trauma, infection, and aging affect people's health and quality of life. The prevalence of bone-related diseases has been increasing yearly in recent years. Mild bone diseases can still be treated with conservative drugs and can be cured confidently. However, serious bone injuries caused by large-scale trauma, fractures, bone tumors, and other diseases are challenging to heal on their own. Open surgery must be used for intervention. The treatment method also faces the problems of a long cycle, high cost, and serious side effects. Studies have found that hydrogels have attracted much attention due to their good biocompatibility and biodegradability and show great potential in treating bone-related diseases. This paper mainly introduces the properties and preparation methods of hydrogels, reviews the application of hydrogels in bone-related diseases (including bone defects, bone fracture, cartilage injuries, and osteosarcoma) in recent years. We also put forward suggestions according to the current development status, pointing out a new direction for developing high-performance hydrogels more suitable for bone-related diseases.